Pendidikan Kewarganegaraan persekolahan: standar isi dan pembelajarannya - Winarno, Winarno (Jurnal Civics: Media Kajian Kewarganegaraan, 2006)
The content standard of civic education for the elementary level and junior high level consist of minimum materials and minimum competency, there are standard competency and basic competency of civic education subject that should be studied by the students. The next definition of contain standard is to arrange Curriculum of Educational Level, syllabi, and Study Implementation Planning. The Civic Education learning stand on the process standard that is the learning process that done interactively, inspirationally, fon, challenging, motivating the student to be actively participated; and also give enough spaces for the initiates, creatively, and independency based on the talent, enthusiasm, and the student physical and development: Substantially, the Civic Education contains, according to the contain standard are similar with the subject contain of the Civic Education based on the 2004 Curriculum. Thereby, the Civic Education teachers can use the 2004 Civic Education Curriculum guide in order to develop the materials and the school Civic Education Learning.